Competitive adsorption of Pb2+, Cd2+ and Zn2+ ions onto Eichhornia crassipes in binary and ternary systems - Mahamadi, Courtie; Nharingo, Tichaona (Elsevier, 2016)
A batch sorption technique was used to study the biosorption of Pb2+, Cd2+ and Zn2+ ions onto the vastly abundant water hyacinth weed, Eichhornia crassipes biomass in binary and ternary systems at a temperature of 30 C and pH 4.84. Mutual interference effects were probed using equilibrium adsorption capacity ratios, q0 e=qe, where the prime indicates the presence of one or two other metal ions. The combined action of the metals was found to be antagonistic, and the metal sorption followed the order Pb2+ Cd2+ Zn2+. The behaviour of competitive biosorption for Pb–Cd and Pb–Zn combinations were successfully described by the Langmuir Competitive Model (CLM), whilst the model showed poor fitting to the Cd–Zn data. In conclusion, Pb2+ ions could still be effectively removed from aqueous solution in the presence of both Cd2+ and Zn2+ ions, but removal of the Cd2+ and Zn2+ ions would be suppressed in the presence of Pb2+.